Efektivitas Iklan Politik Humas Departemen Pertanian: Politik Pencitraan atau Pembentukan Ruang Publik ? - Sarwoprasodjo, Sarwititi (Sodality: Jurnal Sosiologi Pedesaan, 2009)
The objective of this article is to show how political advertisement as published by public relation activities has a deep effect on the change of farmers’ welfare image. The study was carried out to see how far the message contained in political advertisement been in contradictive with farmers’ public opinion. The contradiction normally appeared due to the ways the message was packaged. Normally the message was felt to be very plain as they were built by government and political interest, and bureaucratic flavors. Meanwhile public opinion was normally built in the fortitude of criticizing the government. Public opinion was also influenced by social status, gender, as well as social and political economic context as normally faced by their day to day life. Theoretical implication of this study is, that political advertisement concept needs to integrate participatory development communication. Some practical implication of the study showed that public relation activity needs to integrate development communication concept as well as good governance principles as they became most important Indonesian Government political jargons. Methodologically, this research has an important implication on how to measure government pubic relation effectiveness under good governance framework.